2017
DOI: 10.1088/1742-5468/aa9680
|View full text |Cite
|
Sign up to set email alerts
|

A strong invariance principle for the elephant random walk

Abstract: We consider a non-Markovian discrete-time random walk on Z with unbounded memory called the elephant random walk (ERW). We prove a strong invariance principle for the ERW. More specifically, we prove that, under a suitable scaling and in the diffusive regime as well as at the critical value pc = 3/4 where the model is marginally superdiffusive, the ERW is almost surely well approximated by a Brownian motion. As a by-product of our result we get the law of iterated logarithm and the central limit theorem for th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 14 publications
1
44
0
1
Order By: Relevance
“…The following theorems are generalizations of the results obtained in [1,2,7,8] for the original elephant random walk, although they are essentially proved in existing literatures ( [15,19] among others) for the correlated Bernoulli process. To make this paper reasonably self-contained, we indicate the main lines of proofs in section 3.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…The following theorems are generalizations of the results obtained in [1,2,7,8] for the original elephant random walk, although they are essentially proved in existing literatures ( [15,19] among others) for the correlated Bernoulli process. To make this paper reasonably self-contained, we indicate the main lines of proofs in section 3.…”
Section: Resultsmentioning
confidence: 79%
“…On the other hand, if α > 1/2, then {M n } is an L 2bounded martingale, and the martingale convergence theorem shows that S n /n α converges to a non-degenerate random variable with mean β Γ(α+1) , whose distribution turns out to be non-Gaussian (see [2,3] among others), a.s. and in L 2 . These and further strong limit theorems are obtained by [1,2,7,8]. Kürsten [17] relates the phase transition described above to the behavior of a spin system on random recursive trees.…”
Section: Introductionmentioning
confidence: 93%
“…These results have also appeared more recently in the framework of the so-called elephant random walk, a random walk with memory which has been introduced by Schütz and Trimper [27]. See notably [2,3,11,12], and also [4,5,14,15] and references therein for some further developments. We mention that Kürsten [23] first pointed at the role of Bernoulli bond percolation on random recursive trees in this framework, see also [10].…”
Section: Relation To Step Reinforced Random Walksmentioning
confidence: 86%
“…Initially, the distribution was thought to be normal (i.e. Gaussian) irrespective of the value of  ; subsequently it was found that it is actually non-Gaussian in the super-diffusion regime, although it is difficult to be specific and this is a topic of continuing research [13][14][15][16][17][18][19]. Minor modifications to the original formulation lead to sub-diffusion as well as super-diffusion [20,21], and various other models turn out to have a close connection to the ERW as well, see e.g.…”
mentioning
confidence: 99%